Project-Based Learning on Student's Creative Thinking Skills: Effectiveness and Student Response in Learning Environmental Change - Ristanto, Rizhal Hendi; Hilaliah, Nurlaelatul; Azrai, Eka Putri; Rini, Daniar Setyo; Safitri, Dini (Bioeducation Journal, 2024)
Project-based learning trains creative thinking skills by means of the creation of valued recycling products from inorganic waste. The study aims to discover the improvement of creative thinking skills in environmental change content through project-based learning. The study uses a quasi-experiment method with a pretest-posttest control group design. The instrument used is the creative thinking skill test by referring to Torrence indicators that consist of fluency, flexibility, originality, and elaboration. The test comprises 10 valid question items and has criteria of very high reliability. The study is conducted in Grade X of MIPA in one of the senior high schools (SMA) in Bekasi, Indonesia. The experimental class is taught with a project-based learning model, whereas the control class used conventional learning. Students involved in the research are 76 students in Senir High School 4 Bekasi. Simple random sampling is employed as the sampling technique. Normality test that uses Kolmogorov-Smirnov and homogenity test that employs Levene test indicates that data are normally distributed and homogenous. The results of hypothesis testing suggest an influence on creative thinking skills in environmental change content after the application of the project-based learning. According to the normalized gain calculation, the application of project-based learning has a moderate category. The research finding suggeststhat the learning about environmental changes for students could be taught using project-based learning to empower creative thinking skills.